IMPLEMENTATION OF THE CTL MODEL TO IMPROVE ELEMENTARY SCHOOL STUDENTS' SCIENCE LEARNING OUTCOMES - rizki mutazam ahmad (Teaching and General Education Studies, 2026)
This study examines the implementation of the Contextual Teaching and Learning (CTL) model in Natural Science (IPA) instruction and evaluates its effectiveness in improving elementary school students’ learning outcomes. The study is grounded in the problem of low science achievement among students, which is primarily caused by teacher-centered learning practices that limit students’ active engagement and understanding of scientific concepts. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was conducted in two cycles comprising planning, action, observation, and reflection stages. The subjects of this study were elementary school students who had not yet achieved the Minimum Competency Criteria (KKM) in science learning. Data were collected through classroom observations, interviews, documentation, and achievement tests to obtain comprehensive information on both the learning process and learning outcomes. The results demonstrate a significant improvement in students’ science learning outcomes following the implementation of the CTL model. In the initial condition, most students scored below the KKM. After the first cycle, the learning completion rate reached 44%, indicating a moderate improvement. Subsequent revisions to the learning process through the systematic application of CTL components, including constructivism, inquiry, questioning, learning communities, modeling, reflection, and authentic assessment, led to a substantial increase in learning outcomes in the second cycle, with mastery learning reaching 88%. These findings indicate that CTL effectively promotes active learning, contextual understanding, and the ability to relate scientific concepts to real-life situations. In conclusion, the Contextual Teaching and Learning model is effective in improving elementary school students’ science learning outcomes. This study provides practical benefits for teachers by offering an alternative instructional approach that supports active, meaningful, and student-centered learning in elementary science classrooms.